(3Hjf GdfLa hdHfGfs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi Hf LYaQ cGTa GdZWGA, J (B1350 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3SjZGOQ GdYQGb QEdi dHfGf MLI GdESdGe SeGMI GdEeGe BjI Gddg GdYXei GdTjN Ydj cGTa GdZWGA hPdc dZQV GdeYGdLI hGdaMU (B...s
(3BNQgG (B:s
.. (3GdNdGa GdCSGSj Hjf SjGSI GdOhdI GddHfGfjI heNWWGJ Yed GdHYK aj LejY GdTDhf GdOGNdjI hGdNGQLjI (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdSjGSI hGdGLJeGYs